Microbiome Analysis and Pharmacovigilance After Inhaled Glucocorticoid: Oral Dysbiosis With the Isolation of Three Rothia Species and Subsequent Sjögren’s Syndrome - Zdziarski, Przemysław; Paściak, Mariola; Gamian, Andrzej (Frontiers in Pharmacology, 2022)
Background: Treatment of respiratory tract diseases with inhaled glucocorticoids is a form of therapy that has been used for many years. It shows lower potency of side effects; nevertheless, microbiome change, sinopulmonary dysbiosis, secondary immunodeficiency, and immunomodulatory effects are underestimated. The latest guideline recommendations introduce the use of empirical antibiotic and/or multiplying inhaled glucocorticoids in therapeutic intervention of asthma and chronic pulmonary obstructive disease. Aims and objectives: The aim of the study was to describe a simple, universal, and cost-effective method of microbiome analysis for clinical trials. Such a general method for monitoring pharmacovigilance should be widely available and reliable. Methods: The study material included two kinds of swabs, taken from the same mouth ulcerations of patients with asthma treated with a temporary quadruple dose of fluticasone. The microbiological investigation was performed, and identification of the isolates was carried out using the matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF-MS) Biotyper. Results: The analysis of dry swab demonstrated the presence of typical oral bacteria (Neisseria spp. and Streptococcus spp.), alongside with the potentially pathogenic Actinomyces spp. and three different Rothia species, identified simultaneously: R. aeria, R. dentocariosa, and R. mucilaginosa. Although quadrupled dose of corticoids was discontinued and ulcer healing was observed, the patients required topical therapy for maintained xerostomia. Progressive systemic autoimmunity (seronegative Sjögren’s syndrome with major organ involvement) was observed later. Conclusion: Topical steroids (especially in quadruple dose) require attention to safety, immunomodulation, and microbiological outcome. They showed systemic side effects: microbiome alteration, humoral (IgG) immunodeficiency, and systemic autoimmunity. Isolation of three species of Rothia from a patient with mouth ulcers after steroid therapy suggests their participation in infectious and inflammatory processes. The proposed a methodology using MALDI-TOF-MS may be a prototype approach for microbial diagnostics in clinical trials of immunomodulatory drugs.